Comparison of once a day and three times a day iron treatment in 9-12 year old elementary school children with iron deficiency anemia - Dedy Gunadi; Nelly Rosdiana; Bidasari Lubis (Paediatrica Indonesiana, 2009)
Background The compliance of iron deficiency anemia treatmentthat is administered three times daily in children is low. Thecompliance will be better if therapy is administered once daily.Objective To compare the iron therapy response of once per dayvs. three times a day administration in 9-12 year old children withiron deficiency anemia.Methods Children with iron deficiency anemia were randomlyallocated into a ferrous sulfate once-daily group or a ferrous sulfatethree times-daily group with the same dose of 5 mg/kg /day ofelemental iron for 30 days. Iron deficiency anemia was definedas Hb < 12 g/dL (World Health Organization criteria), MCV< 70 fl, RDW > 16 %, Mentzer index > 13 and RDW index >220. Iron treatment response was characterized by the increase inHb level 30 days after treatment. Peripheral blood samples werecollected at the start and end of the study.Results Ninety seven children were enrolled. There weresignificant increases in Hb levels in both groups after 30 days ofiron therapy, but there was no significant difference in Hb levelbetween the two groups (P=0.55).Conclusion The administration of a once daily dose of ferroussulfate did not show a significant difference in the increase ofHblevels compared to a three times daily dose.